Estudo da utilização de objetos simuladores de polietileno preenchidos com água em medidas de doses periféricas de radioterapia - Soboll, Danyel Scheidegger (2010)
Humanoid phantoms, made of polyethylene and filled with water, were developed for the use in peripheral dosimetry in radiotherapy. Three of them represent infants of different sizes (2, 5 and 10 years) and three are adult size (female in early pregnancy, late pregnancy and one male). It were compared the peripheral doses from two adult male phantoms, the humanoid and an Alderson, submitted to a radiotherapy cranial beam. For 18 MV beams the doses in anthropomorphic were higher within the range of 2.5 to 27%, except for the dose in the heart, about 40% higher in anthropomorphic, due to the fact that in the humanoid region corresponding to lungs is filled with water. For 15 MV the difference decreased and for 6 MV there was an intertwining of the curves of the doses of both phantoms. In regions close to the beam the doses differed by up to 13%, which allows the humanoid phantom to be used to estimate doses in the regions where induction of cancer by radiation occurs more often. In more remote regions, the differences observed in the comparison of doses between the phantoms can be taken into account when the humanoid phantom is used. The humanoid phantom has the advantages of being lightweight and easy handling as well as its low cost. The uncertainties in dosimetry grow with increasing distance from the beam - in the thyroid was observed uncertainty of 0.7% and 5% in the testes. In peripheral pediatric dosimetry during the application of different clinical techniques for cranial treatments, the dose to the thyroid, compared to the dose delivered to the isocenter, was 0.2% for radiosurgery with cone or mMLC, 0.28% in IMRT sliding window, 1.4% in IMRT step and shoot, 2.9% for compensator-based IMRT and 0.23% in VMAT. It was observed that the positioning verification for cranial treatment added 0.13 cGy to the thyroid, for each pair of double-exposure portals. The fetal dosimetry in the treatment of breast cancer showed that different field settings and accessories produce quite different peripheral doses. The presence of wedge filter in the treatment of breast cancer increased by up to four times the fetal doses in the region and it is important to use a lead shield in the abdomen region, because with it the attenuation of radiation is significant and the embryo / fetus can be protected. It is recommended to use humanoid phantoms in the estimation of doses, in order to conduct clinical staff to choose the best treatment technique, create protective shields or even transfer the patient to a more suitable machine.